ANÁLISIS Y DISEÑO DE UN APLICATIVO MÓVIL ANDROID DE RECEPCIÓN DE DATOS EN DISPOSITIVOS PDA ENLAZADO A UN SISTEMA DE ADMINISTRACIÓN DE ENVÍOS PARA SERPOST S.A.C - CORRALES HUAMAN, BEATRIZ LISSET (2021)
This research work focuses on the issue of control of parcel shipments of the SERPOST Company and aims to design and implement an application to improve the shipping management process. The Company does not have the adequate tools to carry out a mobile control of the shipment management process. The main characteristic of this type of control is that the Company's workers will be able to obtain a better control in the management of parcel delivery due to the fact that it does not currently have an application that can verify the physical address, the location, the recipient and the can make a better inventory. In chapter I, the reality of the project under study is identified to pose the problem, the objectives, the justification and the limitation of the research. In chapter II, the international and national antecedents that coincide with the proposed investigation are mentioned to ensure that it is carried out. In chapter III, the research methodology is carried out for an integration plan, study of the approach, scope of the project and variables. In chapter IV, the results obtained in the analysis are displayed, culminating in the discussions. In chapter V the hypothesis testing is carried out, and finally the conclusions and recommendations for the project are shown.. Keywords: Mobile Application, SERPOST, Processes, PDA Device.